Why share premises?: the organisational development process of the House for Health - Beller, Annelie; Rutgers, Michael; Thümler, Ekkehard (Voluntary sector review, 2014)
Collaboration among charities has no value in itself; it needs to respond to specific organisational or societal needs. This article draws on a case study of the House for Health, a consortium of five charities in the Netherlands that share premises. It asks how this particular arrangement - can be made instrumental to fostering the charities' missions. We find that its greatest value is to enable collective organisational learning, and discuss implications and options for implementation.